Adherence to insulin therapy in type 2 diabetes mellitus patients treated at the government’s primary health care centers in Klang, Selangor - Nasruddin , Azri (2017)
Insulin therapy is necessary for Type 2 Diabetes Mellitus (T2DM) patients to accomplish targeted glycaemic level and to prevent diabetes-related complications. This study aimed to determine the proportion of adherence to insulin therapy in patients who attended Ministry of Health’s primary care centers and its associated factors. The association between adherence level and glycaemic control was also studied. This cross-sectional study was conducted among T2DM patients aged 18 years and above and who were on insulin therapy for at least two months. A purposive sampling method was used. This study involved 249 subjects from five Ministry of Health’s primary care centers in Klang. Patients were interviewed, and records were accessed to collect data on socio-demographic characteristics, disease-related factors, treatment-related factors and clinical parameters. A self-administered validated questionnaire was used. Significantly associated factors were identified by using Binary Logistic Regression. The proportion of adherence to insulin therapy was only 8.43% (95% CI: 0.05, 0.12).After adjusting for confounders, three variables were found to be significant. Factors associated with insulin adherence were self monitoring of blood glucose (SMBG) (Adjusted OR=5.39, 95% CI: 1.20, 24.13),exercise (Adjusted OR=3.38, 95% CI: 1.37, 10.03), and number of daily insulin injections (Adjusted OR=1.63, 95% CI: 1.09, 2.44). There was no association between adherence level and glycaemic parameters. Insulin therapy was poor. Patient who practiced SMBG, exercised and had more frequent daily insulin injections significantly affected the adherence to insulin therapy. T2DM patients’ clinical outcomes could be improved through a better and specific identification of factors that could lead to the adherence to insulin therapy.